THE MODERN CONCEPT OF "TOLERANCE" PHILOSOPHICAL DEFINITION - Mamasaliev , Mirzoulug' (Journal of Social Sciences, 2024)
Interethnic harmony and religious tolerance are among the basic principles of a democratic society. Tolerance ensures harmony between citizens, does not allow aggravation of social and national differences. And also protects society from the occurrence of such conflicts. Today, not only in our country, but throughout the world, religious tolerance, interfaith mutual respect, and understanding of each other are becoming the basic principles of life. The true essence of the reforms carried out in our country is also aimed at further increasing the international prestige of the Republic of Uzbekistan. This gives our country, focused on interethnic harmony and religious tolerance, the conduct of a foreign policy in accordance with the national interests of Uzbekistan. The article is devoted to the analysis of modern practices of introducing tolerance in societies with liberal ideology. It is based on the opinion that the modern practice of tolerance in the West does not lead to individual changes in society, but to the formation of a new social reality. The following signs of a change in social reality are identified: a change in norms and values, a change in social consciousness, the transformation of the majority into a minority, a change in the system of social management. The article emphasizes the manipulative nature of the tolerance practices of the modern West, which, under the guise of a noble idea, forms a “new normal” in accordance with the “great reset”.